Cognitive ability and academic achievement of undergraduates - Chong, Yi Long (Serials Publications, 2016)
This study aims to identify cognitive ability and academic achievement of undergraduates in Universiti Teknologi Malaysia. In this study, cognitive ability is a combination of critical thinking, creative thinking, metacognition, and knowledge. A total of 336 undergraduates had participated in this study. Inferential analysis was used to explore the relationship between cognitive abilities and academic achievement of the respondents. The findings showed significant relationship between all cognitive abilities except knowledge and academic achievement. The multiple regression results showed that critical thinking, creative thinking, and metacognition has significant predictive power on undergraduates' academic performance with F (3,332) = 185.909, p < 0.001. Critical thinking has the highest predictive power (β = 0.491) while creative thinking has the lowest predictive power (β = 0.221) on academic achievement. Future study can be done by applying group difference in order to understand more about the development of cognitive abilities among undergraduates.